Genomes, expression profiles, and diversity of mitochondria of the White-footed Deermouse Peromyscus leucopus, reservoir of Lyme disease and other zoonoses - Barbour, Alan G. (Sci Rep, 2019)
The cricetine rodents Peromyscus leucopus and P. maniculatus are key reservoirs for several zoonotic diseases in North America. We determined the complete circular mitochondrial genome sequences of representatives of 3 different stock colonies of P. leucopus, one stock colony of P. maniculatus and two wild populations of P. leucopus. The genomes were syntenic with that of the murids Mus musculus and Rattus norvegicus. Phylogenetic analysis confirmed that these two Peromyscus species are sister taxa in a clade with P. polionotus and also uncovered a distinction between P. leucopus populations in the eastern and the central United States. In one P. leucopus lineage four extended regions of mitochondrial pseudogenes were identified in the nuclear genome. RNA-seq analysis revealed transcription of the entire genome and differences from controls in the expression profiles of mitochondrial genes in the blood, but not in liver or brain, of animals infected with the zoonotic pathogen Borrelia hermsii. PCR and sequencing of the D-loop of the mitochondrion identified 32 different haplotypes among 118 wild P. leucopus at a Connecticut field site. These findings help to further establish P. leucopus as a model organism for studies of emerging infectious diseases, ecology, and in other disciplines.